Marketing Model of EMC Hospital during COVID-19 Pandemic - Liwaul Liwaul; Hasto Joko Nur Utomo; Sutiyana Fachruddin; Renil Septiano; Laynita Sari (Jurnal Komunikasi Profesional, 2022)
After facing COVID-19 Pandemic, the first thing to be recovered is the hospital and health industry. In order to do so, the improvement of International hospital needs to be studied for the next advancement. The dimension that covers international hospital is the label, sustainable marketing and their social media contents that is to be explored in order to discover something. The advancement of it needs to discover their model of marketing first in order to improve the industry. From the syntax to semantic we could able to perceive the quality of the international standard based on social media content as well as the data aid of related theories and various marketing and financial data that serves as pieces of the path of advanced health and hospital industry recovery after suffering the struggle of COVID-19 Pandemic.